Wheat Production in India: Current Studies for the Future - Singh, Bahaderjeet; Kaur, Ramandeep (International Journal of Psychosocial Rehabilitation, 2021)
A staple food for humans and livestock alike, wheat is a major crop in temperate regions. The adaptability and high return capability of wheat are two significant variables in its prosperity. What's more, the gluten protein part, which gives the visco-flexible properties that permit its mixture to be handled into bread, pasta and other food items. It adds supplements, helpful phytochemicals, and dietary fiber parts to the human eating routine. Among the current and future worries examined in this survey are ways of keeping up with wheat creation and quality with lower contributions of agrochemicals, as well as ways of creating work on quality lines for explicit end utilizes, for example, biofuels and human food